Exploring research and education opportunities in digital health for pharmacy, medicine and other health disciplines: Insights from a multinational workshop - Emina Obarcanin; Parisa Aslani; Andy H.Y. Ho; Carole Bandiera; Melissa Baysari; Iva Bojic; Adeola Bamgboje-Ayodele; Qi Chwen Ong; Heiko Spallek; Ronald J. Clarke; Stephanie Läer (Elsevier, 2024)
Digital healthcare has rapidly evolved during and in the post-COVID pandemic era, expanding the roles and responsibilities of community pharmacists. Services like telepharmacy, e-prescriptions, remote medication therapy management, and digital monitoring of chronic conditions, have evolved into everyday routine pharmacy practices. Pharmacists are at the forefront and the most accessible healthcare professionals for patients and are increasingly pivotal in providing comprehensive patient care, including digital patient care services. To ensure that future generations of pharmacists are digitally competent, it is crucial that digital health education is provided to pharmacy students. Furthermore, fostering high-quality multidisciplinary research, particularly in collaboration with medicine and other health disciplines, is essential for advancing the digital health skills of the future pharmacy workforce. Despite the growing use of digital health technologies, there are significant between-country differences in digital health education, the clinical settings in which digital health technologies are used, and their implementation in day-to-day practice. This commentary summarizes key insights from the International Digital Health Workshop held at the University of Sydney in November 2023. To help ensure pharmacists are included as participants in future digital health research, recent advances in digital health education and interprofessional research projects across three universities from far-off world regions were presented. Participants discussed a possible collaborative, interprofessional, and international research project on chronic disease prevention using digital health technologies. The need for interdisciplinary digital health curricula was highlighted in the workshop discussions, specifically tailored to address the knowledge requirements of pharmacists and other healthcare professionals.